Sustainable rural development indicators in Bulgaria, Germany, Poland, Romania and the Netherlands: a review of data - Memo, Umutcan; Pieńkowski, Dariusz (Frontiers in Environmental Science, 2023)
This study examines indices of sustainable rural development in Bulgaria, Germany, Poland, Romania and the Netherlands. The European Union has consistently supported its policy on sustainable rural development and allocated budgetary funds to provide financial assistance. The energy crisis that followed the outbreak of the Russia-Ukraine conflict prompted the European Union to adopt stricter measures regarding sustainable development and energy. To achieve these objectives, it is crucial to accurately identify regional issues and ensure that the established goals are practical and achievable. Some European Union countries have made significant progress in this direction, while others have yet to do so. Therefore, this study is aimed to examine the differences and difficulties of rural development in selected countries of the European Union through data and literature review methods. In the study, the data on population, GDP per capita, greenhouse gas (GHG) emissions, the economic impact of agriculture, and renewable energy are compared for the countries selected at the rural areas and the data on employment, poverty levels, education and rural digitization are compared. The Netherlands and Germany exhibit adherence to the goals of sustainable rural development, while Poland has made progress in several areas towards sustainable rural development. In contrast, according to the study, Bulgaria and Romania require more significant measures to achieve sustainable rural development. Although both countries have some strengths, it is imperative that all relevant parties participate in the process to ensure sustainability. Education is a crucial prerequisite for rural development. However, the percentage of educated individuals in these countries has decreased. Furthermore, it is crucial to provide rural areas with information about digitization and establish the required infrastructure. Moreover, the adoption of smart villages should be considered as a solution, in which all stakeholders can efficiently benefit from education and digitization, and sustainable resources can be developed.